Catalytic Hydrogenation for Biomass Valorization (ProtoView, 2015)
The editor has organized the contributions that make up the main body of the text in thirteen chapters devoted to the economics and role of hydrogen in biorefining, the general reaction mechanisms in hydrogenation and hydrogenolysis for biorefining, solvents and solvent effects in biomass conversion, and a wide variety of other related subjects.